Can Sildenafil Citrate Be a Game Changer in the Management of Tuberculosis? A Food for Thought? - Hameed, Najma; Farooq, Khalid (Biological and Clinical Sciences Research Journal, 2025)
Isoniazid (INH) and Rifampicin (RIF) are cornerstone drugs in tuberculosis therapy but are known to cause hepatotoxicity. Sildenafil citrate, a phosphodiesterase-5 inhibitor, has shown potential antioxidant and anti-inflammatory properties, yet its hepatoprotective effects have not been extensively evaluated. Objective: To investigate the biochemical changes induced by combined INH-RIF therapy and assess the potential hepatoprotective effects of sildenafil treatment in a murine model. Methods: This randomized experimental study involved 21 Swiss albino mice (25–35 g), divided into three groups (n=7 each) using simple balloting. Group C (control) received 0.4 mL/kg normal saline intraperitoneally for 21 days. Group R (INH-RIF) was administered isoniazid and rifampicin (50 mg/kg each) intraperitoneally, daily for 21 days. Group S (INH-RIF + Sildenafil) received the same INH-RIF regimen with concurrent oral sildenafil (10 mg/kg) via gastric gavage. At the end of treatment, serum liver function tests (LFTs) were analyzed. Data were processed using descriptive statistics; inter-group differences were assessed using appropriate statistical tests with significance set at p < 0.05. Results: Group R exhibited significant elevation in serum hepatic enzymes indicating hepatotoxicity. Group S showed marked improvement in LFT parameters compared to Group R, suggesting attenuation of hepatotoxicity. Group C maintained normal hepatic profiles. Sildenafil administration resulted in a statistically significant reduction in biochemical markers of liver injury. Conclusion: Sildenafil citrate demonstrates a protective role against INH-RIF-induced hepatotoxicity, supporting its potential therapeutic use in minimizing anti-tuberculous drug-induced liver injury.